Antagonistic Potential Marine Bacteria Against Luminescent Vibriosis Pathogen Vibrio Harveyi Obtained from Shrimp Farm, Marakkanam, Tamil Nadu, India: Life Sciences-Microbiology - Sakthivel, Murugan; Jayanthi, Jayaprakash; Gurunathan Ragunathan, Manickavalli (International Journal of Life Science and Pharma Research, 2022)
Aquaculture farming practices in India and other countries are facing a lot of economic loss due to luminescent vibriosis. Ecological and cost-effective practices may have been warranted to combat this tricky disease. A total of 57 morphologically different marine bacterial isolates were isolated from samples collected at different aquaculture ponds in Marakkanam, Tamil Nadu, India and screened for their antibacterial potential against luminescent vibriosis causing bacteria Vibrio harveyi. All marine bacterial isolates were screened for antibacterial activity by cross streak method against two different isolates V. harveyi GNC01 and V. harveyi GNC03. Secondary screening of antagonistic isolates by dual culture plate method and agar well diffusion method leads to the identification of antagonistic isolates. The antagonistic isolates were characterized by molecular taxonomy (16S rRNA gene sequence) and phylogeny and identified as Neobacillus niacini (GNC04), Bacillus halotolerans (GNC06), Bacillus amyloliquefaciens (GNC16), Lacticaseibacillus paracasei (GNC23) and Lactiplantibacillus plantarum (GNC24). The minimum inhibitory concentration of all these selected bacterial crude secondary metabolites against both Vibrio harveyi isolates GNC01 and GNC03 ranged between 0.062 to 0.50 mg/mL. The GC-MS profiling of the ethyl acetate extract revealed the presence of antibacterial compounds such as Oxime-,methoxy-phenyl (26.63%), 2,3-Dihydroxybutane (9.52%), Phosphite, menthyldimethyl- (2.83%), Pyrrolo[1,2-a]pyrazine- 1,4-dione, hexahydro-3-(2-methylpropyl)- (2.07%). The results of this study suggest that Lactiplantibacillus plantarum (GNC24) is a potential source for antagonistic secondary metabolites against luminescent vibriosis causing bacteria Vibrio harveyi. Further, biological control formulation with these isolates and their metabolites will be a reward for the integrated pest management in the aquaculture sector.